Atopic dermatitis is not independently associated with nonfatal myocardial infarction or stroke among US women. Issue 10 (20th July 2016) - Drucker, A. M.; Li, W.‐Q.; Cho, E.; Li, T.; Sun, Q.; Camargo, C. A.; Qureshi, A. A.
Abstract: We aimed to determine the association between atopic dermatitis (AD) and cardiovascular events in the Nurses' Health Study 2, a cohort of US women. We used logistic regression models to calculate age‐ and multivariate‐adjusted odds ratios (OR) and 95% confidence intervals (CI) for the associations between history of AD and nonfatal MI and nonfatal stroke. Of the 78 702 participants in our analysis, 7916 (10%) had a history of AD. There were 392 and 391 cases of nonfatal MI and stroke, respectively. AD was not associated with MI in age‐ or multivariate‐adjusted analyses. AD was significantly associated with stroke in the age‐adjusted analysis (OR 1.38, 95% CI 1.03–1.85). This was no longer significant in multivariate models that adjusted for hypertension, hypercholesterolemia and diabetes (OR 1.31, 95% CI 0.98–1.76) and atopic comorbidities (OR 1.17, 95% CI 0.86–1.58). AD was not independently associated with nonfatal MI or stroke in this study.